A ubiquitin ligase-associated chaperone holdase maintains polypeptides in soluble states for proteasome degradation - Wang, Qiuyan (2011)
Endoplasmic reticulum-associated degradation (ERAD) employs membrane-bound ubiquitin ligases and the translocation-driving ATPase p97 to retrotranslocate misfolded proteins for proteasomal degradation. How retrotranslocated polypeptides bearing exposed hydrophobic motifs or transmembrane domains (TMD) avoid aggregation before reaching the proteasome is unclear. Here we identify a ubiquitin ligase-associated multiprotein complex comprising Bag6, Ubl4A, and Trc35, which chaperones retrotranslocated polypeptides en route to the proteasome to improve ERAD efficiency. In vitro, Bag6, the central component of the complex, contains a chaperone-like activity capable of maintaining an aggregation-prone substrate in an unfolded yet soluble state. The physiological importance of this holdase activity is underscored by observations that ERAD substrates accumulate in detergent insoluble aggregates in cells depleted of Bag6, or of Trc35, a cofactor that keeps Bag6 outside the nucleus for engagement in ERAD. Our results reveal a ubiquitin ligase-associated holdase that maintains polypeptide solubility to enhance protein quality control in mammalian cells.